IMPLEMENTASI MANAJEMEN PEMBELAJARAN PPKn KURIKULUM 2013 - Rahmayani Rahmayani Rahmayani (UNIVERSITAS BENGKULU, 2016)
The purpose of research was to describe the implementation of instructional management of Civics subject of the 2013-Curriculum at Grade VII of Public Junior High SchoolNumber 1 of Bengkulu City. This study employed the qualitative descriptive research method. The data were collected by applying the observation, interviews, and documentation. The results show that the implementation of instructional management in Civics subject of the 2013-Curriculum atGrade VII of Public Junior High School Number 1 of Bengkulu City have complied with standard stages of instructional management; they are planning of the instructional process, implementation of the instructional process, and evaluation of the instructional results. The school principal, the vice principals, the teachers, and the students have considerably understood the vision, missions, and aims of the Civics subject of the 2013-Curriculum.Keywords: Implementation, instructional management, Civics Subject, the, 2013-Curriculum